Ukraine's gas sector - Pirani, S (Oxford Institute for Energy Studies, 2007)
The paper aims to provide an overview of the Ukrainian gas sector. Public discussion in western Europe has turned to Ukraine as a transit country – through which more than four-fifths of Russian gas exports to Europe pass – when its disputes with Russia have threatened to interrupt supply. Such an occasion was in the first week of January 2006. Pressure was reduced in some pipelines, pending resolution of that year’s particularly bitter dispute.